Modeling the Process of Business Management Systems Control - Milan Majernik; Naqib Daneshjo; Katarina Repkova Stofkova (Communications - Scientific letters of the University of Zilina, 2016)
Innovative trends in production management increasingly involve implementation and auditing of standardized management systems according to ISO standards. Within the paper are presented the results of research focused on optimization of auditing system processes in the area of quality, environment and safety. There was constructed an algorithm and quantified mathematical model of integrated auditing and using Gantt chart, the visualization of annual auditing plan was realized. Verified and validated proposed model offers possibilities of its extending for the capacity management and indicators of integrated auditing processes of business management systems.